Polymorphisms of TLR4 but not CD14 are associated with a decreased risk of aggressive periodontitis - Jacqueline A. James (Blackwell Synergy, 2007)
Objective: To study whether there is an association between the frequency of functional polymorphisms in the toll-like receptor 4 (TLR4) and cluster differentiation 14 (CD14) genes and periodontitis. Methodology: Genotyping for the TLR4 single-nucleotide polymorphisms (SNPs) Asp299Gly, Thr399Ile and the CD14 SNPs 159 and 1359 was completed for subjects with periodontal disease compared with control subjects. Two disease populations were investigated: 73 subjects with aggressive periodontitis (AgP; 28 males, 45 females) and 95 males with chronic periodontitis (CP). The TLR4 and CD14 polymorphisms were determined using SNaPshot primer extension with capillary electrophoresis. Comparison of allele and genotype frequencies for each polymorphism was by Fisher’s exact test or w2 analysis. Results: The TLR4 Asp299Gly genotype was present in a significantly (p50.026) lower proportion of AgP subjects (5.5%) compared with control subjects (16.3%). The unadjusted odds ratio for the Asp299Gly genotype to be associated with AgP was 0.30, 95% confidence interval 0.10–0.91. No differences were found in the prevalence of the TLR4 Asp299Gly genotype in men with CP (18.9%) compared with an age-matched control group with no evidence of periodontitis (17%). In addition, there was no difference in the distribution of the CD14 polymorphisms in either the AgP or CP populations studied compared with controls.